Extra cardiac perforation following failed percutaneous transvenous mitral commissurotomy - T. R., Sunil Kumar; Karthik Kumar; Mahesh Kumar, Aishwarya (International Surgery Journal, 2023)
Percutaneous transvenous mitral commissurotomy (PTMC) is the procedure of choice for select patients with mitral valve disease who have favorable valve architecture and meet the requirements for balloon valve dilatation. Complications following PTMC are rare (<3%). A 56-year-old woman with rheumatic valvular heart disease, severe mitral stenosis and moderate mitral regurgitation in atrial fibrillation underwent elective PTMC. She developed an extra-cardiac perforation during PTMC because of abnormal catheter course, and underwent emergency mitral valve replacement with extra-cardiac perforation repair. Catheter-related complications following PTMC are rare but not unheard of. Prompt management of immediate complications result in favorable outcomes.